Outlier Detection using Clustering Techniques - ., Srividya; Mohanavalli, S; Sripriya, N; Poornima, S (International Journal of Engineering and Technology, 2018)
An outlier is nothing but a pattern that is different compared to the other existingÂ  patterns in a particular dataset. In some applications it is very important to understand and identify outliers. Detecting outlier is of major importance in many of the fields like cybersecurity, machine learning, finance, healthcare, etc., A clustering based method is proposed to detect outliers using different algorithms like k means, PAM, Clara, DBScan and LOF on different data sets like breast cancer, heart diseases, multi shaped datasets. This work aims to identify the best suitable method to detect the outliners accurately. Â Â
Keywords: Outliner Detection; Data Mining; K Means; LOF; CLARA